Integration of Payload Sensors to Enhance UAV-Based Spraying - Barcelos, Celso O. (2024)
This work focuses on the use of load sensors to help with spraying tasks using unmannedaerial vehicles (UAVs). The study details the construction of a prototype for load measurement tovalidate the proof of concept. To simulate the application of agricultural pesticides, the UAV followsa predefined route and an image processing system detects the presence of diseased plants. Afterdetection, the UAV pauses its route momentarily and activates the spraying device. The payloadsensor monitors the fertilizer application process, which determines whether the amount of pesticide has been fully applied. If the storage tank is empty or the remaining quantity is insufficient for another operation, the system will command the UAV to return to the base station for refueling.Experimental validations were carried out in an indoor controlled environment to verify the proposaland the functionality of the in-flight payload monitoring system. Additionally, the UAV’s flightcontroller demonstrated robust performance, maintaining stability despite the challenges posed byliquid-load oscillations and varying payloads during the spraying process. In summary, our maincontribution is a real-time payload monitoring system that monitors weight during flight to avoidover- or under-spraying. In addition, this system supports automatic refueling, detecting low levelsof pesticides and directing the UAV to return to base when necessary.